Examining Cultural Competency and Sexual Abuse Training Needs among Service Providers Working with Black and Latino Sexual Minority Men. Issue 49 (2nd January 2023) - Downing,, Martin J.; Benoit, Ellen; Coe, Lauren; Brown, Dominique; Steen, Jeffrey T.
Abstract: Black and Latino sexual minority men (SMM) with a history of childhood sexual abuse (CSA) may be reluctant to disclose such experiences or may appraise them as consensual because of cultural norms. Anticipated stigma, medical mistrust, and concerns that providers lack training in sexuality may complicate their efforts to obtain treatment for long-term health consequences of CSA. It is important to examine the training needs of service providers working with SMM who may disclose sexual abuse. Qualitative interviews were conducted with 35 substance use disorder (SUD) treatment and allied health service providers across the New York City area. Themes included the importance of training in cultural competence, trauma-informed care, and assessment of—and counseling for—CSA. Further education in these areas can enable providers to recognize indicators of abuse in their clients' sexual histories and to more effectively and safely respond to this information. Future studies are encouraged to test a trauma-informed approach to screening for CSA history with Black and Latino SMM who present to SUD treatment and allied health service providers. This research should consider provider perspectives in developing such an approach and will likely involve training and evaluation to ensure adequate preparedness and effective service delivery.